ANALISIS PENGENDALIAN INTERNAL PADA IMPLEMENTASI ANGGARAN KEGIATAN LIDIK DALAM MENUNJANG EFEKTIVITAS PENGELOLAAN ADMINISTRASI - Prabowo, Rachmad Gesah Mukti; Hariyanti, Tiwuk Puji; Marlena, Marlena (LPPM STIE Muhammadiah Bandung, 2021)
Budgeting is very important in an organization, the budget as a control tool indicates the allocation of public funding sources contained in the regional budget, it will be seen whether the budget that has been made can act as a controller for the implementation of government activities. This study identifies and analyzes the internal control system of the budget implementation process for the investigation and investigation activities at the Responsibility Mountain Police, Tulungagung Regency. Using qualitative descriptive methods, assisted by making question guides to stay focused on the discussion. The results of the study stated that the SOP was in accordance with its function, although for certain cases outside the planning, sometimes the realization was not appropriate because the disbursement was sometimes late.